Effect of Hypoxia Preconditioned Adipose-Derived Mesenchymal Stem Cell Conditioned Medium on Cerulein-Induced Acute Pancreatitis in Mice - Kamal Abdolmohammadi; Tayebeh Mahmoudi; Shahrzad Nojehdehi; Lobat Tayebi; Seyed Mahmoud Hashemi; Farshid Noorbakhsh; Alireza Abdollahi; Masoud Soleimani; Behrouz Nikbin; Mohammad Hossein Nicknam (Tabriz University of Medical Sciences, 2020)
Purpose: Acute pancreatitis (AP) is an inflammatory disorder distinguished by tissue injury and inflammation of the pancreas. Using paracrine potential of mesenchymal stem cells (MSCs) provides a useful clinical approach in treating inflammatory diseases. We investigated the therapeutic effects of adipose-derived MSC conditioned medium (CM) and hypoxia preconditioned adipose-derived MSC conditioned medium (HCM) in cerulein-induced AP in mice. Methods: AP was induced in C57BL/6 mice by intraperitoneal injection of cerulein (75 μg/ kg/h × 7 times). One hour following the last injection of cerulein, mice were treated with intraperitoneal injection of CM and HCM (500 µL/mice/30 min × 3 times). Twelve hours following the treatment, serum levels of amylase and lipase were measured. In addition, pancreas pathological changes, immunohistochemical examinations for evaluation of IL-6 expression and pancreatic myeloperoxidase (MPO) enzyme activity were analyzed. Results: The in vitro results of the morphological, differentiation and immunophenotyping analyses confirmed that hypoxia preconditioned MSCs (HP-MSCs) conserve MSCs characteristics after preconditioning. However, HP-MSCs significantly expressed high mRNA level of hypoxia inducible factor 1-α and higher level of total protein. The in vivo findings of the current study showed that CM and HCM significantly reduced the amylase & lipase activity, the severity of pancreas tissue injury and the expression of IL-6 and MPO enzyme activity compared with the AP group. However, no significant difference between CM and HCM groups was demonstrated. Conclusion: Use of CM and HCM can attenuate cerulein-induced AP and decrease inflammation in the pancreas tissue in AP mice.